2010
DOI: 10.1371/journal.pone.0013989
|View full text |Cite
|
Sign up to set email alerts
|

APP Processing Induced by Herpes Simplex Virus Type 1 (HSV-1) Yields Several APP Fragments in Human and Rat Neuronal Cells

Abstract: Lifelong latent infections of the trigeminal ganglion by the neurotropic herpes simplex virus type 1 (HSV-1) are characterized by periodic reactivation. During these episodes, newly produced virions may also reach the central nervous system (CNS), causing productive but generally asymptomatic infections. Epidemiological and experimental findings suggest that HSV-1 might contribute to the pathogenesis of Alzheimer's disease (AD). This multifactorial neurodegenerative disorder is related to an overproduction of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

7
129
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 125 publications
(137 citation statements)
references
References 52 publications
7
129
0
1
Order By: Relevance
“…Freeze-dried purified A␤40, A␤42, A␤42-1, and A␤42 variant harboring oxidized methionine at position 35 (A␤42 MO ) and human amylin were purchased from AnaSpec. Protein solutions were prepared as previously described (Piacentini et al, 2008a;De Chiara et al, 2010;Maiti et al, 2011;Attar et al, 2012; according to standard procedures. Briefly, peptides were diluted to 1 mM in 1,1,1,3,3,3,-hexafluoro-2-propanol to disassemble preformed aggregates and stored as dry films at Ϫ20°C before use.…”
Section: Methodsmentioning
confidence: 99%
“…Freeze-dried purified A␤40, A␤42, A␤42-1, and A␤42 variant harboring oxidized methionine at position 35 (A␤42 MO ) and human amylin were purchased from AnaSpec. Protein solutions were prepared as previously described (Piacentini et al, 2008a;De Chiara et al, 2010;Maiti et al, 2011;Attar et al, 2012; according to standard procedures. Briefly, peptides were diluted to 1 mM in 1,1,1,3,3,3,-hexafluoro-2-propanol to disassemble preformed aggregates and stored as dry films at Ϫ20°C before use.…”
Section: Methodsmentioning
confidence: 99%
“…The presence of a possible connection between HSV-1 and AD was first suggested more than 30 years ago [8]. This suggestion was subsequently strengthened by a number of in vitro data indicating that HSV-1 infection of neuron cell lines results in the same molecular alterations that are observed in AD, including APP processing [9] and intracellular distribution [10], and τ protein phosphorylation [11]. Notably, the possible connection between HSV-1 and AD has also been reinforced over the years by a number of epidemiological results (for a very recent state-of-the art document, see: Itzhaki et al 2016 [12]).…”
mentioning
confidence: 97%
“…All these diseases can develop decades after the primary infection. Molecular evidences show that HSV-1 infection of neuronal and glial cells results in an increase of the intracellular levels of b amyloid (Ab), a decrease of the amyloid precursor protein and the phosphorylation of Tau protein, the main component of neurofibrillary tangles [8][9][10][11]: these are the same cellular events associated with the development of AD. Recent results have also demonstrated that the interaction between amyloid precursor protein and the HSV-1 capsid proteins [12] is essential to allow the migration of new viral particles inside infected cells.…”
mentioning
confidence: 99%